Brasil, Moçambique e Angola: desvendando relações sociolinguísticas pelo prisma das formas de tratamento - Balsalobre, Sabrina Rodrigues Garcia [UNESP] (2015)
A common heritage underlies between Brazil, Mozambique and Angola (in addition to other Portuguese-speaking African countries: Cape Verde, Sao Tome and Principe and Guinea Bissau) that persists to the present with varying degrees of intensity and national representation: the Portuguese language. With such different forms of use, the Portuguese contributes to the development of national identity in each of these countries. Thereby, this work aims to comparatively evaluate the system of addressing forms of the Brazilian, Mozambican and Angolan Portuguese varieties. Thus, the addressing forms chosen by country users over others assist in the analysis of interrelationships between language and society, revealing foundations of social organization. For this purpose, the addressing system of three varieties of Portuguese language in question was analyzed based on two macro divisions: the nominal and the pronominal forms. Once that is in focus the investigation of the language and its social motivators, the approach underlying this analysis is the Sociolinguistics. In addition, is also in focus a pragmatic look at the data. Associated with this theoretical perspective, different approaches of power are still on focus and also the theory of kinship that permeates linguistic choices. In order to achieve the addressing forms 73 people were interviewed, split between São Paulo (Brazil), Maputo (Mozambique) and Luanda (Angola). In these interviews, the goal was to capture the different addressing strategies produced by the informants in relation to different social profiles that were presented to them by photographs of people. Once structured the corpus, a comparison was made between the results presented in each country, revealing: i) the addressing forms shared by the three countries because of the common Portuguese matrix, such as dona, senhor(a), moço(a); ii) the specific relational forms of each country, considering its social peculiarities...